2017
DOI: 10.1097/ccm.0000000000002305
|View full text |Cite
|
Sign up to set email alerts
|

The Economic and Clinical Impact of Sustained Use of a Progressive Mobility Program in a Neuro-ICU*

Abstract: An ongoing progressive mobility program in the neurocritical care population has clinical and financial benefits associated with its implementation and should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…These results may be associated with an insufficient sample size to detect a statistical difference for these secondary outcomes. Accordingly, a retrospective study with a large sample size (1118 neurocritical patients) demonstrated the significant impact of early rehabilitation for shortening ICU and hospital stays with a mean difference of 0.7 and 2.7 days respectively [53].…”
Section: Discussionmentioning
confidence: 99%
“…These results may be associated with an insufficient sample size to detect a statistical difference for these secondary outcomes. Accordingly, a retrospective study with a large sample size (1118 neurocritical patients) demonstrated the significant impact of early rehabilitation for shortening ICU and hospital stays with a mean difference of 0.7 and 2.7 days respectively [53].…”
Section: Discussionmentioning
confidence: 99%
“…High protocol compliance resulted in a significant 9-hour LOS reduction per hospitalization as well as a shift in unit culture 19 . This result was supported by a separate study that implemented the Progressive Upright Mobility Protocol Plus, emphasizing nursing education implementation in neurosurgical care 28 . Additional outcomes included decreased hospital-acquired infections and associated medical costs 19 …”
Section: Resultsmentioning
confidence: 91%
“…27 There are studies pertaining to nurse-driven teamwork. 7,16,17,19,20,28,29 Researchers developed a protocol to mobilize neurosurgical spine patients, in which nurses and patient care technicians independently led mobilization. Nurse practitioners or physicians adjusted medications if pain hindered mobility efforts.…”
Section: Teamwork In Mobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissemination of our objective review will be imperative to enhance clinical practice and evaluate the different components of the ABCDEF bundle, and hopefully to quantify the impact of bundle implementation to the various outcomes we have described. Some bundle components have been shown to have an economic benefit [ 61 ], and as researchers contribute to the collective growing body of knowledge, we anticipate that changes in practice will soon become the standard of care.…”
Section: Discussionmentioning
confidence: 99%